WEBSITE CREATING AND MANAGEMENT TRAINING NULISH INSTITUTE AS INFORMATION MEDIA - Maududi, Mukhlish Muhammad; Nusivera, Egi; Romadlan, Said (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Lack of knowledge about the Benefits of The Website as an Information medium and the absence of Website management skills are the problems partners are trying to solve, so the purpose of the Community Service Program is to increase Partner Knowledge about the Benefits of Websites as Information Media and Provide Website Management Skills so that it becomes a medium for Partner publications to the wider community, the Proposing Team collaborates with the Nulish Institute Foundation. The method used in community service is in the form of a lecture method, the resource persons provide an explanation of the importance of the website and how to operationalize and manage the website as an information medium, then a discussion is held to multiply from the participants about what information can be managed to be published on the website by combining photos and text, as well as practicing how to operate the website starting from logging in and uploading data into a website, finally, an evaluation was carried out by observing participants regarding the achievement of the objectives of community service activities, the implementation of this training was considered successfully carried out due to the increase in Partner knowledge, and the increase in Partner skills in using the Website, participants were able to upload content to the website.